Therapeutic Potential of Exosomes Derived From circRNA_0002113 Lacking Mesenchymal Stem Cells in Myocardial Infarction - Tian, Tiantian; Li, Feng; Chen, Ruihua; Wang, Zhiwei; Su, Xueming; Yang, Chao (Frontiers in Cell and Developmental Biology, 2022)
Exosomes are participated in the pathogenesis of cardiovascular diseases and can be secreted by mesenchymal stem cells (MSCs). However, the effects of circRNA, delivered by exosomes derived from MSCs, on myocardial injury remain unclear. Hence, this study aims to explore the therapeutic potential of exosomes derived from circRNA_0002113 lacking MSCs in the treatment of myocardial injury in vitro and in vivo. Our results reveal that exosomes derived from circRNA_0002113 lacking MSCs decreased cell apoptosis in anoxia-reoxygenation (A/R) model cells, and reduced myocardial injury by inhibiting nuclear translocation of RUNX1 in vitro and in vivo. Moreover, miR-188-3p, which targets RUNX1 in cardiomyocytes was also found to interact with circRNA_0002113. In conclusion, exosomes derived from circRNA_0002113 lacking MSCs could suppress myocardial infarction by sponging miR-188-3p to regulate RUNX1 nuclear translocation. The circRNA_0002113/miR-188-3p/RUNX1 axis mediated alleviation of apoptosis serves as a novel strategy to treat myocardial I/R injury.